2018
DOI: 10.1037/men0000119
|View full text |Cite
|
Sign up to set email alerts
|

Eating meat makes you sexy: Conformity to dietary gender norms and attractiveness.

Abstract: Past research has highlighted links between meat consumption and masculine gender role norms such that meat consumers are generally attributed more masculine traits than their vegetable-consuming counterparts. However, the direct link between gender roles and men’s food choices has been somewhat neglected in the literature. Three studies conducted in Italy investigated this link between meat and masculinity. Studies 1 and 2 analyzed female mating preference for vegetarian and omnivorous partners, confirming th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Personality was defined as the totality of the personal, characteristic, and individual qualities of a person. Only the individual values of a person were relevant for this work, not social values and norms (e.g., the link between meat and masculinity in Timeo and Suitner, 2017). Additionally, it should be noted again that, in most of the included studies, the proportion of women was higher than that of men.…”
Section: Limitationsmentioning
confidence: 99%
“…Personality was defined as the totality of the personal, characteristic, and individual qualities of a person. Only the individual values of a person were relevant for this work, not social values and norms (e.g., the link between meat and masculinity in Timeo and Suitner, 2017). Additionally, it should be noted again that, in most of the included studies, the proportion of women was higher than that of men.…”
Section: Limitationsmentioning
confidence: 99%
“…These observations are borne out by empirical research. Studies conducted in Italy showed that women preferred omnivorous men, rated them as more attractive and felt more positive about them than about vegetarians [51]. The participants were asked to evaluate 6 different profiles (3 vegetarians, 3 omnivorous) of male targets (age, height, weight, profession, hobbies, eating habits and favorite dishes).…”
Section: Evaluation Of Masculinity and Attractiveness Of Vegans/vegetmentioning
confidence: 99%
“…Although previous investigations in Costa Rica and elsewhere (Arganini et al, 2012 ; Carey et al, 2017 ; Cavazza et al, 2015a ; Kimura et al, 2009 , 2011 ; Monge-Rojas et al, 2015 ; Vartanian et al, 2007 ; Young et al, 2009 ) concluded that adolescents consider unhealthy foods as ‘masculine’ and healthy foods as ‘feminine,’ future research would benefit from a more detailed examination of this attributional process, segregated by sex and by specific food items. In other countries, studies have included the task of rating how ‘masculine’ or ‘feminine’ participants consider specific food items (Cavazza et al, 2015b ; Timeo & Suitner, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, since adolescents might be quite sensitive to social norms (Lombardi, Coley, Sims, Lynch, & Mahalik, 2019 ), it is particularly valuable to develop a better scientific understanding of gender-based stereotypes and their role in the establishment of unhealthy eating habits during this period of life. Several studies (Herman et al, 2019 ; Igenoza, 2017 ; Le, 2019 ; Timeo & Suitner, 2018 ) have shown that eating-related traditional femininity victimize girls into stereotypical body shapes and harmful weight-control behaviors (like dietary restraint). On the other hand, the high-energy-dense foods related to masculinity make adolescent boys more susceptible to developing a deleterious lipid profile and overweight/obesity in the short term.…”
Section: Introductionmentioning
confidence: 99%